Importance and implementation of safe nursing behaviors in nursing students’ clinical practice: Importance–Performance Analysis (IPA), the borich needs assessment model, and the locus for focus model - Eunjung Kim; Hae Ran Kim (PLoS ONE, 2026)
Background Nursing students are exposed to diverse occupational risks during clinical practicum, which may threaten both their safety and patient safety. Despite the increasing emphasis on safety education following the Patient Safety Act in South Korea, few studies have examined their performance and perceived importance of safe nursing behaviors. This study addresses this gap to provide evidence for improving nursing safety education. Methods A cross-sectional survey was conducted among 160 nursing students from two universities in South Korea who had completed their clinical practicums. Data were collected using a self-administered 29-item questionnaire developed through a literature review and expert validation. It comprises four domains: infection prevention, musculoskeletal injury prevention, chemical hazard prevention, and psychological injury prevention. Data analysis was performed using SPSS/WIN 28.0, including descriptive statistics, paired-sample t-tests, independent t-tests, and one-way ANOVA. Priority analysis was conducted using Importance-Performance Analysis (IPA), the Borich Needs Assessment model, and the Locus for Focus model. Results Importance scores were significantly higher than performance scores across most items, except for “Dispose used ampoules/needles without recapping” and “Dispose sharps into puncture-resistant containers.” IPA identified 14 items in the “Keep up the good work” quadrant and four items in the “Concentrate here” quadrant. The Borich Needs Assessment model ranked “Know the location of spill kits,” “Use devices to reduce musculoskeletal load” and “Use of goggles when biological exposure is possible” as having the highest priorities. The Locus for Focus model classified five items, including personal protective equipment (PPE) use during biological exposure, maintain posture during ergonomic risks, chemical education, and respect for personal dignity, as the top priority (HH quadrant) for educational intervention. Conclusions The assessment tool effectively evaluated nursing students’ safe nursing behaviors during clinical practicums. Four domain-specific priorities were identified: personal protective equipment (PPE) use in infection prevention, ergonomic safety practices, chemical safety knowledge, and psychological safety measures. These findings provide evidence-based guidance for designing targeted and practical nursing safety education programs to improve nursing students’ preparedness, safety, and patient safety.